2010
DOI: 10.1007/s00586-010-1394-x
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of artificial total disc replacement versus fusion for lumbar degenerative disc disease

Abstract: Lumbar fusion has been developed for several decades and became the standard surgical treatment for symptomatic lumbar degenerative disc disease (DDD). Artificial total disc replacement (TDR), as an alternative for spinal arthrodesis, is becoming more commonly employed treating lumbar DDD. It is still uncertain whether TDR is more effective and safer than lumbar fusion. To systematically compare the effectiveness and safety of TDR to that of the fusion for the treatment of lumbar DDD, we performed a meta-analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 50 publications
(90 reference statements)
0
46
1
Order By: Relevance
“…(13) In a meta-analysis of ADR versus fusion for lumbar DDD, Yajun et al also noted better postoperative functional status (with less back and leg pain) and higher satisfaction rates in the ADR group than in the lumbar fusion group at the two-year follow-up. (21) As the measures of disability, pain and neurological status were similarly improved from baseline in both the ADR and TLIF groups at five years after treatment, some authors have concluded that ADR surgery using ProDisc-L was not inferior to fusion surgery in the treatment of single-level lumbar DDD. (22) Although the short-and mid-term results of ADR have been shown to be positive, the long-term benefit of ADR surgery over fusion surgery in lumbar DDD has not been proven conclusively.…”
Section: Discussionmentioning
confidence: 91%
“…(13) In a meta-analysis of ADR versus fusion for lumbar DDD, Yajun et al also noted better postoperative functional status (with less back and leg pain) and higher satisfaction rates in the ADR group than in the lumbar fusion group at the two-year follow-up. (21) As the measures of disability, pain and neurological status were similarly improved from baseline in both the ADR and TLIF groups at five years after treatment, some authors have concluded that ADR surgery using ProDisc-L was not inferior to fusion surgery in the treatment of single-level lumbar DDD. (22) Although the short-and mid-term results of ADR have been shown to be positive, the long-term benefit of ADR surgery over fusion surgery in lumbar DDD has not been proven conclusively.…”
Section: Discussionmentioning
confidence: 91%
“…Evidence from several studies shows that arthroplasty is superior to fusion and conservative care [18][19][20][32][33][34]. The activL Artificial Disc is the latest evolution of TDR devices for arthroplasty that further advances mechanical motion-preservation in the lumbar spine.…”
Section: Discussionmentioning
confidence: 99%
“…Across several outcomes such as disability, pain and patient satisfaction, improvements were statistically significantly in favor of TDR compared with fusion [18][19][20][32][33][34]. Furthermore, TDR was demonstrated to have either similar or improved safety compared with fusion, as typically measured by total complications, reoperation rates and adjacent segment degeneration [18][19][20][32][33][34]36,37]. When compared with conservative care, TDR showed greater improvements in disability, pain and quality of life [32].…”
Section: Discussionmentioning
confidence: 99%
“…However, meta-analyses of randomized controlled trials (RCTs), representing the highest level of evidence, have been published to compare lumbar TDR with fusion for lumbar DDD [37][38][39][40][41]. The findings of these meta-analyses are conflicting and thereby result in uncertainty for decision makers.…”
Section: Successes and Obstacles To Widespread Adoptionmentioning
confidence: 99%